REDUPLIKASI KATA BERIMBUHAN BAHASA MELAYU TERNATE - Fachmi Alhadar; Rudi S. Tawari (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This article studies the reduplication process of Malay Ternate (BMT). The process of reduplication when compared to Indonesian, has a uniqueness that is not found in Indonesian. By using qualitative methods, this study describes the process of reduplication and its implications for BMT. Reduplication of affixed word in the Malay Ternate can occur multiple times. In the type of verb that forms the verb "ba", reduplication can occur up to three times, either on prefix reduplication, basic word reduplication, and full affixed word reduplication. While the reduplication of verbs with the prefix "ma" only occur twice reduplication, those are in the prefix and full affixed word. For the word "ta", the implication of the word class is to be an adjective class. In reduplication with the prefix "ta", the average occur three times reduplication, namely in the prefix, base word, and full affixed word. This study shows that any word that is reduplicated up to three times due to the basic word can be used independently in BMT or not bound to the prefix. While the word that is always bounds to the prefix in its use has a chance of reduplication only twice.